2016
DOI: 10.1111/geoj.12188
|View full text |Cite
|
Sign up to set email alerts
|

The relational character of urban agriculture: competing perspectives on land, food, people, agriculture and the city

Abstract: In recent years the diverse primary food production activities in cities known as ‘urban agriculture’ have proliferated on the ground, in policy and in academic discourse. Most explicit representations of urban agriculture (UA) are positive, advocating its many related benefits and success stories, or critiquing barriers that restrict it. Despite widespread appeal, the way UA is imagined and planned remains highly varied and uncertain. To understand better the splintering and insular discourses and competing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 37 publications
0
5
0
2
Order By: Relevance
“…These two frames of motivations align with the lenses of "food" and "people" as discussed by Neilson and Rickards (2017) with regard to urban agriculture. Sonti and Svendsen (2018) also showed that healthy food has grown as an urban agriculture motivation since the early 2000s, while community improvement motivations have lessened over that time period.…”
Section: Discussionmentioning
confidence: 63%
“…These two frames of motivations align with the lenses of "food" and "people" as discussed by Neilson and Rickards (2017) with regard to urban agriculture. Sonti and Svendsen (2018) also showed that healthy food has grown as an urban agriculture motivation since the early 2000s, while community improvement motivations have lessened over that time period.…”
Section: Discussionmentioning
confidence: 63%
“…Research on UA has generally tended to take an advocacy viewpoint (Neilson and Rickards, 2017), which might have led to overstating its potential in some cases, in turn attracting criticism. Badami & Ramankutty (2015) found that the contribution of UA to the food security of the urban poor is quite low, despite the strongest need.…”
Section: Realistic Lens: Advocacy and Oppositionmentioning
confidence: 99%
“…En tercer lugar, con base en los puntos anteriores, este estudio proporciona nuevos argumentos para la protección y promoción de la APU, particularmente en el Sur Global. Aunque la agricultura urbana a menudo es medida en términos de productividad, tanto por quienes se oponen como por los que la defienden (Neilson;Rickards, 2017), este estudio proporciona evidencia en apoyo a los impactos benéficos, no económicos y de difícil cuantificación, de la APU en la construcción del sentido de propósito, tejido social y resiliencia de las comunidades locales. Además -y lo que es más importante-, este estudio hace evidente cómo estos logros no son el resultado del activismo ambiental o agrícola o de intervenciones públicas, sino que surgen de prácticas normales generalizadas en las comunidades locales.…”
Section: Contribución a La Literatura Sobre Agricultura Periurbana Y unclassified
“…Tanto los que se oponen como los que defienden la agricultura urbana a menudo miden sus impactos únicamente en términos de productividad material (Neilson;Rickards, 2017); estas evaluaciones limitadas a los valores monetarios han chocado con contribuciones difícilmente cuantificables como el capital simbólico del autoabastecimiento de alimentos, y su apego y reinvención de las herencias e identidades campesinas (Cantor, 2010;Méndez;Ramírez;Alzate, 2005;Sahakian et al, 2016). A su vez, desafíos en la medición de la agricultura urbana han contribuido a su invisibilidad en los documentos de planificación territorial y en el ámbito de la formulación de políticas públicas, en particular desde las perspectivas social y cultural (Feola;Suzunaga;Soler;Goodman, 2019;Ives;Kendal, 2013;Nadal et al, 2018).…”
Section: Introductionunclassified